Fenomenologi Minat Beli Ulang Produk Kesehatan: Kajian atas Kesesuaian Biaya-Manfaat, Keberagaman Varian dan Pengalaman Konsumsi - Didit Darmawan; Ardava Auwiby Muhammad (Universitas Batanghari, 2026)
This literature study aims to analyze the meaning of cost-benefit fit, appreciation for product variety, and reflection on consumption experience in shaping repurchase intention of health products from a phenomenological perspective. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that cost-benefit fit is subjectively interpreted through comparisons between sacrifices made and physical and psychological benefits received. Consumers who perceive proportional value develop satisfaction that drives repurchase intention. Appreciation for product variety reflects consumer needs for choices aligned with individual preferences, creating emotional bonds with brands. Reflection on consumption experience becomes a cumulative evaluation process where consumers recall, compare, and assess each interaction with the product. These three aspects are interconnected in forming the meaning of repurchase intention that is personal and dynamic. Consumers with diverse positive experiences across product variants develop strong emotional attachments to brands. Repurchase becomes not merely a transaction but a ritual that reinforces identity and brand relationships. This study contributes theoretically to enriching consumer behavior literature through a phenomenological perspective and practically provides foundations for manufacturers in designing products and communication strategies aligned with consumer meaning-making processes.